Role of Pathogenicity Determinant Protein C (PdpC) in Determining the Virulence of the Francisella tularensis Subspecies tularensis SCHU - Uda, Akihiko (Public Library of Science, 2014)
Francisella tularensis subspecies tularensis, the etiological agent of tularemia, is highly pathogenic to humans and animals. However, the SCHU strain of F. tularensis SCHU P0 maintained by passaging in artificial media has been found to be attenuated. To better understand the molecular mechanisms behind the pathogenicity of F. tularensis SCHU, we attempted to isolate virulent bacteria by serial passages in mice. SCHU P5 obtained after 5th passages in mice remained avirulent, while SCHU P9 obtained after 9th passages was completely virulent in mice. Moreover, SCHU P9 grew more efficiently in J774.1 murine macrophages compared with that in the less pathogenic SCHU P0 and P5. Comparison of the nucleotide sequences of the whole genomes of SCHU P0, P5, and P9 revealed only 1 nucleotide difference among P0, P5 and P9 in 1 of the 2 copies of pathogenicity determinant protein C (pdpC) gene. An adenine residue deletion was observed in the pdpC1 gene of SCHU P0, P5, and P9 and in the pdpC2 gene of SCHU P0, and P5, while P9 was characterized by the wild type pdpC2 gene. Thus, SCHU P0 and P5 expressed only truncated forms of PdpC protein, while SCHU P9 expressed both wild type and truncated versions. To validate the pathogenicity of PdpC, both copies of the pdpC gene in SCHU P9 have been inactivated by Targetron mutagenesis. SCHU P9 mutants with inactivated pdpC gene showed low intracellular growth in J774.1 cells and did not induce severe disease in experimentally infected mice, while virulence of the mutants was restored by complementation with expression of the intact PdpC. These results demonstrate that PdpC is crucial in determining the virulence of F. tularensis SCHU.